A multiplicity of approaches to institutional analysis : applications to the government and the arts - Bruno S. Frey (Center for Economic Studies and ifo Institute (CESifo), 2009)
Four types of economics relevant for institutional analysis are distinguished: Standard Neoclassical Economics; Socio-Economics or Social Economics; New Institutional Economics; and Psychological Economics (often misleadingly called Behavioural Economics). The paper argues that an extension of Neoclassical Economics with elements from other social sciences (including political science, sociology, psychology, law and anthropology) is fruitful to explain institutions because it allows us to maintain the strength of that approach. Social Economics can play an important role helping to overcome the limitations of Neoclassics. However, it should become more concrete, integrate what is useful in Neoclassics, and should seriously engage in empirical research.
Keywords: H77; P16; Z11; 330; Institutional Economics; Neoclassics; Psychological Economics; Behavioural Economics; institutions; Institutionalismus; Neue Institutionenökonomik; Neoklassik; Verhaltensökonomik; Wirtschaftspsychologie; Sozialökonomik; Public Choice; Kulturökonomik; Theorie